Helical β‐isoindigo‐Based Chromophores with B−O−B Bridge: Facile Synthesis and Tunable Near‐Infrared Circularly Polarized Luminescence. (18th January 2023) - Xu, Yongqiang; Ni, Zhigang; Xiao, Yao; Chen, Ziwei; Wang, Sisi; Gai, Lizhi; Zheng, You‐Xuan; Shen, Zhen; Lu, Hua; Guo, Zijian
Abstract: It is essential to create organic compounds that exhibit circularly polarized luminescence (CPL) in the near‐infrared (NIR) range. Helicene‐type emitters possess appealing chiroptical features, however, such NIR molecules are scarce due to a paucity of synthetic strategies. Herein, we developed a series of helical β‐isoindigo‐based B−O−B bridged aza‐BODIPY analogs that were synthesized conveniently. The reaction of diimino‐β‐isoindigo with a heteroaromatic amine produced a restricted ligand cavity, which triggered off the generation of a B−O−B bridge. The B−O−B bridge led to distorted conformations that satisfy the helical requirements, resulting in excellent spectroscopic and chiroptical properties. Tunable CPL with the highest luminescence dissymmetry factor ( g lum ) of 1.3×10 −3 and a CPL brightness ( B CPL =11.5 M −1  cm −1 ) in the NIR region was achieved. This synthetic approach is expected to offer a new opportunity to chiral chemistry and increase flexibility for chiroptical tuning. Abstract : A study of a series of helical β‐isoindigo‐based B−O−B‐bridged chromophores has shown that the bridge leads to distorted conformations. This results in the chromophores having excellent spectroscopic and chiroptical properties, such as tunable circularly polarized luminescence (CPL), with a high luminescence dissymmetry factor ( g lum ) of 1.3×10 −3 and a CPL brightness ( B CPL ) of 11.5 M −1  cm −1 in the near‐infrared region observed for one of the compounds.